An overview about ultrastructure of Kranz anatomy in Cyperaceae (Poales) - Martins, Shirley; Machado, Silvia Rodrigues [UNESP]; Scatena, Vera Lucia [UNESP] (FapUNIFESP (SciELO), 2015)
An overview about ultrastructure of Kranz anatomy in Cyperaceae (Poales) - The ultrastructure of the Kranz tissues in Cyperaceae species with the four types of Kranz anatomy (chlorocyperoid, eleocharoid, fimbristyloid and rhynchosporoid) was studied and compared with species already described in the literature, with the goal verifying the occurrence of patterns for the Kranz types. In addition, chloroplasts and mitochondria were quantified for the first time for all Kranz types. The chloroplast's structure is similar in the mesophyll cells (PCA) in the four Kranz types, but differs in some features in the bundle sheath cells (PCR). In the chlorocyperoid and rhynchosporoid types the bundle sheath cells (PCR) present centrifugal or scattered chloroplasts with convoluted or parallel thylakoids. In the eleocharoid types, the chloroplasts are scattered with parallel thylakoids. The fimbristyloid type presents centrifugal chloroplasts with convoluted and parallel thylakoids. To eleocharoid and fimbristyloid types and to Cyperus and Pycreus (chlorocyperoid) was observed pattern in the chloroplasts position. In most of the studied species the number of mitochondria in the bundle sheath cells (PCR) is significantly higher than in the mesophyll cells (PCA) and this result diverges from the results found in previous studies.
Keywords: C4 photosynthesis; Chloroplast; Cyperaceae; Kranz; Mitochondria